Spinning Wheel Game Media for Fourth Grade Students' Javanese Writing Skills - Fajar Rachma Milenia; Sukardi (Jurnal Edutech Undiksha, 2023)
The limited learning media used by teachers is one of the inhibiting factors in learning Javanese, especially the material for writing Javanese scripts, as evidenced by student scores, which are still below average. As a result, teachers must have teaching media that are varied, innovative, and interesting so that students can learn with focus and enthusiasm, participating in learning and improving students' Javanese script-writing skills. This research aims to develop the Spinning Wheel Game media in Javanese script to improve the writing skills of fourth-grade students. This type of research is R&D development research using the Borg & Gall development model. The subjects in this research are material experts, media experts, class teachers, and students. Data collection methods are observation, interviews, questionnaires, and tests. Data analysis techniques use quantitative descriptive, qualitative descriptive, and inferential statistics. The results of this research are: the design of the Spinning Wheel Game media, the feasibility of the Spinning Wheel Game media based on media experts' responses with a score of 97.5%, and the material expert's assessment of 93.75%, and the effectiveness of the Spinning Wheel Game media using the results of the t-test with The average pretest score was 57.5 and posttest 82.75. The development of Spinning Wheel Game media was feasible and effective for class IV students as a medium for learning Javanese script writing skills.